Conditions for Successful Local Collective Action in Mangrove Forest Management: Some Evidences from Eastern Coastal Area of South Sulawesi, Indonesia. Issue 1 (1st May 2022) - Suharti, S; Darusman, D; Nugroho, B; Sundawati, L
Abstract: Resource management characterized by Common Pool Resources (CPRs) requires collective action for its sustainable management. CPRs with "rivalry" and "non-excludable" features face overexploitation problems because unlike the nature of pure public goods, the use of CPRs by one user will reduce the chances of other users taking advantage of it. This study aims to analyze the most appropriate local institutions and tenure arrangements for sustainable mangrove management in Eastern coast area of South Sulawesi, Indonesia. Data and information were collected through in-depth interviews involving key informants selected by using snow-ball method and continued by Focus Group Discussion. Design principles for sustainable management of common pool resources of Ostrom has been used in this study as an analytical framework which illustrate the structure of rules established and imposed by the local CPR's institutions. The findings show that collective action in sustainable mangrove management can be achieved through accepted rules and agreements that are participatory formulated. The agreed norms and rules have enacted as a benchmark for collective action in maintaining mangrove and to enforce sanctions for violators. The success of the community in sustainable mangrove resources management is mainly supported by the existence of several prerequisites that facilitate collective action. It is necessary to strengthen regulations both at the local and higher level through socialization to the community along with the development of incentive and disincentives system.